1999
DOI: 10.1038/sj.bjc.6690655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of life of cancer patients: assessments by patients, significant others, physicians and nurses

Abstract: Summary This study examined the usefulness of caregiver ratings of cancer patients' quality of life (QOL), an issue of relevance to bot h adequate patient care and to the possible use of proxy QOL raters in clinical studies.We compared QOL ratings of 90 cancer pat ients receiving inpatient chemotherapy with those provided by their significant others (most often the spouse), physicians and nurses . During patients' scheduled appointment for receiving chemotherapy on a clinical ward, all raters completed indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
5
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 37 publications
11
126
5
9
Order By: Relevance
“…This position has been supported by some studies (21) showing slightly higher levels of patient Á/proxy agreement for significant others as compared with either physicians or nurses. However, results from recent studies, performed within inpatient care, indicate that the level of patient Á/physician agreement may only be slightly lower than that of patients and spouses or other close companions (17,22,23). The findings indicate that both significant others and healthcare providers can be useful sources of information about patients' QL.…”
Section: Patient and Proxy Ratings Of Patient Qlmentioning
confidence: 87%
See 1 more Smart Citation
“…This position has been supported by some studies (21) showing slightly higher levels of patient Á/proxy agreement for significant others as compared with either physicians or nurses. However, results from recent studies, performed within inpatient care, indicate that the level of patient Á/physician agreement may only be slightly lower than that of patients and spouses or other close companions (17,22,23). The findings indicate that both significant others and healthcare providers can be useful sources of information about patients' QL.…”
Section: Patient and Proxy Ratings Of Patient Qlmentioning
confidence: 87%
“…When responses from patients, significant others, physicians, and nurses were compared (17), deviant scores of more than one response category appeared to be caused most often by the patients themselves. This might be interpreted as indicating that all proxy raters were unaware of the patients' QL.…”
Section: Patient and Proxy Ratings Of Patient Qlmentioning
confidence: 99%
“…However, the lack of information about measurements with specific QOL instruments in this type of patients impeded its use in the model. Therefore, we believe that utilities values used in this model could be even lower and that results of cost-utility ratios could be even greater than those calculated here (22,23). Finally, costs were calculated using the SOAT manual, that could overestimate them over other costs sources as the ISS manual, but we believe conclusions will not change because the greater cost comes from a device not included in any manual, with similar values for both costs calculation systems.…”
Section: Discussionmentioning
confidence: 89%
“…It has been found that the level of agreement between healthcare providers and patients appears to be dependent on clear questions with a high degree of concreteness and a minimum of subjectivity in the quality of life dimensions assessment. For example, patients' functional status tends to be more accurately rated than patients' level of psychological distress (18)(19)(20).…”
Section: The Patients' Perceptions Of Injections and Therapymentioning
confidence: 99%